Boyz N the Hood / Baby boy (Culver City, California Sony Pictures, 2014)
Boyz N The Hood is the critically-acclaimed story about three friends growing up in a South Central Los Angeles neighborhood. It is a place where harmony co-exists with adversity, especially for three young men growing up there: Doughboy (Ice Cube), an unambitious drug dealer; his brother Ricky (Morris Chestnut), a college-bound teenage father; and Ricky's best friend Tre (Cuba Gooding, Jr. ), who aspires to a brighter future beyond " The Hood." In a world where a trip to the store can end in death, the friends have diverse reactions to their bleak surroundings. Tre's resolve is strengthened by a strong father (Larry Fishburne) who keeps him on the right track. But the lessons Tre learns are put to the ultimate test when tragedy strikes close to home, and violence seems the only recourse.
Jody (Tyrese Gibson) is a 20-year old African American in South Central L.A. who is trying to live large but doesn't have a job. He's got two babies by two different women and still lives at home with his mother (A.J. Johnson). Growing up is tough on Jody, but a series of events involving his mother's new boyfriend Melvin Rodney (Snoop Dogg) forces him to learn lessons about living, loving and surviving as a man in the hood.
112191
Keywords: Family; Friends; Gangs